Transparency and Tacit Collusion in a Differentiated Market - Christian Schultz (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper investigates the effects on tacit collusion of increased market transparency on the consumer side of a market in a differentiated Hotelling duopoly. Increasing market transparency increases the benefits to a firm from underbutting the collusive price. It also decreases the punishment profit. The net effect is that collusion becomes harder to sustain. In the limiting homogeneous market, the effect vanishes. Here market transparency does not affect the possibilities for tacit collusion.
Keywords: 330; transparency; tacit collusion; competition policy; internet